Healthcare financing in Nigeria: the analysis of the inequity perspective (2019)
The volume and quality of healthcare needs vary from one individual to another but promoting access to the use of healthcare is germane to reduce/eliminate inequity in healthcare. This paper examines the extent of equity in healthcare financing in Nigeria, and determine the relative progressivity of each source of healthcare financing in the country using waves 2 and 3 of the General Household Survey. Kakwani and Modified Kakwani (MDK) indexes were used to estimate progressivity of out of pocket payment (OOP) and social health insurance. Overall result indicates a vertical inequity favouring the non-poor (pro-rich), OOP as a source of financing was regressive and social health insurance was moderately progressive. Given that a more progressive healthcare financing approach tends to promote welfare and improve health status of the population, Nigeria will be better off promoting health insurance as a means of eliminating inequity in healthcare financing.